Ballistic Gravimeter of the Poltava Gravimetric Observatory. History of Creation and Modernization - Khalyavin, O.I.; Khalyavina, L.Ya. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2026)
Development of the ballistic gravimeter began at the Poltava Gravimetric Observatory in 1968. After the first prototype was tested in 1972, it was updated further. Lead engineer B.I. Brodsky supervised the work. A highly qualified mechanic, V.A. Ovchinnikov, made significant contributions to the project. By 2000, a working BG-2 prototype had been built; it was equipped with an advanced measurement recording and processing system. Since 2003, regular measurements of the gravity acceleration g had been conducted. The accuracy of these measurements was inferior to that of commercial instruments, prompting continued work on improving BG-2’s key components. Despite the limited accuracy of the results, analysis of a 7-year g data series showed the presence of tidal waves, in particular the semidiurnal lunar M2 wave, demonstrating the feasibility of using the equipment for gravity monitoring. BG-2 resumed operation in 2024. The mechanical and optical units remained unchanged. The control, recording, and measurement processing module was modernized. It is based on an STM32F407VGT6 programmable microcontroller (MCU) (SYSCLC=168 MHz), integrated into the STM32F4-DISCOVERY board, as well an OSC5A2B02 10 MHz temperature-stabilized oscillator for MCU clocking. The MCU’s internal timer polling intervals are monitored. Software for processing measurements and analyzing the obtained results was developed. Trial measurements verified the module’s functionality